Almodóvar on Almodóvar - Almodóvar, Pedro (Faber, 2006)
Pedro Almodovar's influence on European popular culture has been immense. From a small village in rural Spain to international acclaim for his many wonderfully vivid and outrageous films, Almodovar On Almodovar tells the story of the man and his films.